Tensile Testing of 3D Printed Materials Made by Different Temperature - Pernica, Jakub; Sustr, Michal; Dostal, Petr; Brabec, Martin; Dobrocky, David (Manufacturing Technology Journal, 2021)
The work is focused effect of different temperature nozzle in additive manufacturing process FFF (Fused Fila-ment Fabrication) technology for the most common materials (PLA, PETG and ABS). A standard specimen internal structure arranged ±45° in longitudinal print direction with 100% infill. For the exact testing are used no perimetres. The specimens were printed by minimal, middle and maximum nozzle tem-perature. Temperature range is given by the filament company. To ensure relevant testing materials from the same company in one colour were used. A printed specimens were testing by destructive testing method on tensile testing machine. For testing were made five specimens in one setting. Finally, were made 45 specimens for tensile testing.
Keywords: Additive manufacturing; 3D print; FDM/FFF; tensile testing; print nozzle temperature; mechanical properties.